Antibody-catalysed glycosyl transfer reactions from in vitro immunization - Jaehoon Yu; So Young Choi; Sungsoo Lee; Hyun Joo Yoon; Sunjoo Jeong; Hansuh Mun; Hokoon Park; Peter G. Schultz (ROYAL SOC CHEMISTRY, 1997)
In vitro immunization using a 5-membered ring iminocyclitol afforded antibodies that catalyse the hydrolysis of p-nitrophenyl glucopyranoside and p-nitrophenyl galactopyranoside with rate enhancements (k(cat)/k(uncat)) of greater than 10(4).